Thematics : interdisciplinary studies - Louwerse, Max; Peer, Willie van (J. Benjamins Pub. Co., 2002)
Themes play a central role in our everyday communication: we have to know what a text is about in order to understand it. Intended meaning cannot be understood without some knowledge of the underlying theme. This book helps to define the concept of 'themes' in texts and how they are structured in language use. Much of the literature on Thematics is scattered over different disciplines (literature, psychology, linguistics, cognitive science), which this detailed collection pulls together in one coherent overview. The result is a new landmark for the study and understanding of themes in their eve.
Keywords: Comparative literature -- Themes, motives.; Littérature comparée -- Thèmes, motifs.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Comparative literature -- Themes, motives; Diskursanalyse; Rezeption; Literatur; Thema; Thema-Rhema-Gliederung; Kohäsion -- Linguistik; Textkohärenz; Sprachverstehen; Texttheorie; Erzählforschung; Thema (taalkunde); Literaire thema's.